Overweight release agent for optical display, release film and preparation method
By using aqueous chlorinated polypropylene and aqueous polyurethane to prepare the super-weight release film for optical display, the problems of insufficient high temperature resistance and adhesion of the release film in the prior art are solved, and efficient and stable antistatic properties and good bending adaptability are achieved.
Patent Information
- Application Number
- CN202411879636.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The existing release films for optical displays have problems such as silicon transfer, poor high temperature resistance and complex process. The traditional anti-static ionization films have poor aging resistance, easy to attenuate the anti-static effect, and are not easily compatible with silicone oil release agents.
High temperature-resistant release film is made of water-based chlorinated polypropylene, and the toughness of the release film is adjusted by water-based polyurethane, which is suitable for products with different bending degrees. At the same time, the types of raw materials for aqueous polyurethane polymerization are improved and the adhesion between the ultra-thin release layer and the substrate layer is improved.
The high temperature stability and good adhesion of the super heavy release film for optical display are achieved, suitable for products with different bending degrees, and the sustainability of antistatic properties is improved.
Smart Images

Figure BDA0005197868320000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of release films, and in particular to an ultra-heavy release agent for optical display, a release film and a preparation method thereof. Background Art
[0002] The super-heavy release agent for optical display is a special material specially designed to protect and separate sensitive optical components. It must have excellent antistatic properties as well as good mechanical properties and high temperature resistance to ensure that no damage or residue is caused to the protected optical surface when removed. Existing silicone oil release films have defects such as silicon transfer and poor high temperature resistance. Traditional antistatic release films use PEDOT as a functional additive for antistatic coatings, which causes the material to have a blue color and poor aging resistance. After a long time, the antistatic effect will decay, and it is not easy to be compatible with silicone oil release agents. It often requires two processes, first coating the antistatic layer and then coating the release layer. The process is complicated and easy to delaminate.
[0003] Therefore, it is necessary to improve the release film in the prior art. Summary of the invention
[0004] One of the purposes of the present invention is to overcome the defects existing in the prior art and provide an ultra-heavy release agent for optical display. A high-temperature resistant release film is prepared by using water-based chlorinated polypropylene, and the toughness of the release film is adjusted by water-based polyurethane, which is suitable for products with different degrees of bending, and the release film is adjusted to reach the standard of ultra-heavy release force. The type of raw materials for the polymerization of water-based polyurethane is improved to improve the adhesion between the ultra-thin release layer and the substrate layer.
[0005] In order to achieve the above-mentioned process effect, the technical solution of the present invention is: an ultra-heavy release agent for optical display, which comprises, by weight, 10 parts of water-based chlorinated polypropylene, 2 to 4 parts of water-based polyurethane, 0.5 to 0.8 parts of antistatic agent, 0.01 to 0.02 parts of nanocellulose and 4 to 8 parts of solvent;
[0006] The waterborne polyurethane comprises polyethylene terephthalate degradation oligomers, and the polyethylene terephthalate degradation oligomers are hydroxyl-terminated oligomers terminated by neopentyl glycol and / or dipropylene glycol.
[0007] The preferred technical solution is: the antistatic agent is polyaniline doped with camphorsulfonic acid.
[0008] The preferred technical solution is: the nanocellulose is prepared by acid hydrolysis using hydrochloric acid.
[0009] The preferred technical solution is: the waterborne polyurethane is prepared by polyol, polyisocyanate, small molecule chain extender, hydrophilic chain extender, salt-forming agent and first deionized water.
[0010] The preferred technical solution is: the small molecule chain extender is an amine small molecule.
[0011] The preferred technical solution is: the polyol also includes polytetrahydrofuran diol, the polyisocyanate is isophorone diisocyanate, the molar ratio of the polytetrahydrofuran diol to isophorone diisocyanate is 1:(1.15-1.25), and the added amount of the polyethylene terephthalate degradation oligomer is 2.8%-3.5% of the mass of the polyisocyanate.
[0012] The preferred technical solution is: the solvent is isopropanol and a second deionized water, and the mass ratio of the isopropanol to the second deionized water is (2-3):1.
[0013] The second object of the present invention is to overcome the defects in the prior art and provide an ultra-heavy release film for optical display, comprising a substrate layer and a release layer, wherein the release layer is obtained by curing the ultra-heavy release agent for optical display.
[0014] The third object of the present invention is to overcome the defects existing in the prior art and provide a method for preparing an ultra-heavy release film for optical display, comprising the following steps:
[0015] S1: preparing a substrate layer and the above-mentioned super heavy release agent for optical display;
[0016] S2: The super heavy release agent is coated on the surface of the substrate layer to form an uncured release layer;
[0017] S3: Dry and solidify the release layer, and the continuous drying temperatures are set in sequence as follows: 70±5°C, 95±5°C, 110±5°C, 120±5°C, 130±5°C, 95±5°C;
[0018] S4: rolling and aging, wherein the aging temperature is 58-63° C. and the time is more than 24 hours.
[0019] The preferred technical solution is: the thickness of the release layer is 0.5-1 μm.
[0020] The advantages and beneficial effects of the present invention are:
[0021] The release agent uses water-based chlorinated polypropylene to produce a high-temperature resistant release film, which is suitable for optical display applications;
[0022] The toughness of the release film is adjusted by water-based polyurethane, which is suitable for products with different degrees of curvature, and the release film is adjusted to meet the standard of super-heavy release force; and the types of raw materials for water-based polyurethane polymerization are improved to improve the adhesion between the ultra-thin release layer and the substrate layer. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.
[0024] Water-based chlorinated polypropylene
[0025] Chlorinated polypropylene is grafted and modified with acrylate, maleic anhydride, etc., and an amine reagent is added for neutralization, and a water-based chlorinated polypropylene emulsion is prepared by a phase inversion method. Furthermore, the water-based chlorinated polypropylene is Japan Unitika AT-81SD. Pure water-based chlorinated polypropylene has a low surface energy, which makes it an effective release layer that can reduce adhesion with other materials when removed.
[0026] There are two types of molecular segments in water-based chlorinated polypropylene emulsion, one is polar molecular segments, including modified side chains grafted onto the main chain of chlorinated polypropylene, and the other is non-polar molecular segments, which are mainly chlorinated polypropylene molecular chains that have not undergone grafting reaction. According to the principle of similar compatibility, non-polar molecular segments are close to the substrate layer, and non-polar molecular segments are distributed on the surface of the release layer to improve the release force of the release film. However, it fails to meet the requirement of overweight peeling force of more than 150g for optical display. The non-polar molecular segments mainly composed of chlorinated polypropylene have poor adhesion to the PET substrate. When preparing an ultra-thin release layer below 1μm, it is easy to cause delamination between the release layer and the substrate layer. Therefore, water-based polyurethane is added to adjust the release force of the release film and the adhesion between the release layer and the substrate layer.
[0027] Waterborne polyurethane
[0028] Polyethylene terephthalate degradation oligomers are decomposed by using the discarded PET film from the production line in the presence of n-butyl titanate catalyst. The titanium cation center can activate the carbonyl oxygen on the polyester chain, resulting in charge transfer, making the carbonyl carbon atom positively charged. The ester CO bond is then broken through the affinity attack of the hydroxyl groups in neopentyl glycol (NPG) and dipropylene glycol (DPG), generating NPG and / or DPG-terminated hydroxyl-terminated oligomers.
[0029] The polyol includes polytetramethylene glycol, which can increase the viscosity of polyurethane and has excellent properties such as resistance to low temperature, water, oil, wear and mildew.
[0030] The polyisocyanate is isophorone diisocyanate (IPDI). IPDI has two different types of -NCO groups with different group activities. The reaction conditions can be controlled, and the polyol selectively reacts with the -NCO at the aliphatic primary position to form an -NCO-terminated polyurethane prepolymer. The synthesized polyurethane material has excellent optical stability and chemical resistance.
[0031] Small molecule chain extenders make oligomer prepolymer molecular chains grow and increase molecular weight. Chain extenders are small amine molecules, and further, hydrazine and / or ethylenediamine. The primary amine in the amine chain extender has high reactivity with isocyanate to generate polyurethane urea. It is usually added in the polyurethane emulsification and dispersion stage. Due to the strong polarity of the urea group, the synthesized polyurethane material has excellent adhesion and heat resistance.
[0032] The hydrophilic chain extender is 2,2-dimethylol propionic acid, and a relatively small amount thereof can provide sufficient carboxyl groups.
[0033] The salt-forming agent can react with the low-activity carboxyl groups retained by the hydrophilic chain extender to generate ammonium salt or alkali metal salt, thereby improving the hydrophilicity of the molecular chain. Furthermore, the salt-forming agent is triethylamine, and the synthesized polyurethane material has strong stability.
[0034] The preparation method of waterborne polyurethane comprises the following steps: mixing polytetrahydrofuran diol (Mn=2000) and polyethylene terephthalate degradation oligomer, heating to 50°C, adding hexafluoroisopropanol to dissolve and fully mixing and stirring, heating to 80±1°C, adding isophorone diisocyanate IPDI (content ≥99%) to mix, dropping 0.5wt% dibutyltin disilicic acid (DBTDL) catalyst, reacting for 2h; then adding 2,2-dihydroxymethylpropionic acid hydrophilic chain extender solution with a mass of 30% of IPDI mass, continuing to maintain at 80±1°C, reacting for 1h; cooling to 40°C, then adding ethylenediamine chain extender with a mass ratio of 0.14:1 to IPDI to obtain a prepolymer, then adding salt-forming agent triethylamine (TEA) to neutralize to a pH value of 7-8, and adding first deionized water under high-speed stirring for emulsification.
[0035] The molar ratio of the waterborne polyurethane sample 1: polytetramethylene glycol and isophorone diisocyanate is 1:1.2, and the added amount of the polyethylene terephthalate degradation oligomer is 3% of the mass of the polyisocyanate.
[0036] Sample 2 of waterborne polyurethane: the molar ratio of polytetramethylene glycol to isophorone diisocyanate is 1:1.15, and the added amount of polyethylene terephthalate degradation oligomer is 2% of the mass of polyisocyanate.
[0037] Sample 3 of waterborne polyurethane: the molar ratio of polytetramethylene glycol to isophorone diisocyanate is 1:1.22, and the added amount of polyethylene terephthalate degradation oligomer is 4% of the mass of polyisocyanate.
[0038] Sample 4 of waterborne polyurethane: Based on Sample 1, 1,4-butanediol (BDO) chain extender was used instead of ethylenediamine chain extender.
[0039] Sample 5 of waterborne polyurethane: the polyol only includes polytetramethylene glycol and does not include polyethylene terephthalate degradation oligomers. The molar ratio of polytetramethylene glycol to isophorone diisocyanate is 1:1.1.
[0040] Antistatic Agents
[0041] It is polyaniline doped with camphorsulfonic acid. Polyaniline is relatively more stable in the air than polypyrrole, but its solubility is poor. Camphorsulfonic acid (CSA) is used as a dopant. Due to its good solubility characteristics, camphorsulfonic acid can improve the dispersibility and processing performance of polyaniline in the solution. It can also introduce additional positive charges into the polyaniline chain. When the protons (H+) provided by CSA combine with the nitrogen atoms in the polyaniline molecules, positively charged polyaniline salts are formed, thereby increasing the carrier concentration. This doping effect changes the electronic structure of polyaniline, allowing more π electrons to move freely, thereby improving the conductivity of the release layer.
[0042] Preparation method of antistatic agent: polyaniline (particle size 0.1 μm) is first treated with ammonia water and then dispersed in NMP, camphorsulfonic acid is dissolved in N-methylpyrrolidone (NMP), mixed evenly to obtain 10 mg / ml dopant, and then the dopant is added, reacted for more than 48 hours, filtered and dried to obtain the product.
[0043] Nanocellulose
[0044] The preparation methods of nanocellulose can be systematically divided into three categories: chemical method, mechanical method and biological method. Among them, the aspect ratio, size and crystallinity of nanocellulose obtained by chemical method can be selected in a wider range, and the experimental conditions can be adjusted to obtain nanocellulose with different properties. The operation is simple and flexible. Sulfuric acid method, hydrochloric acid method, ammonium persulfate method and TEMPO oxidation method are common chemical methods for preparing nanocellulose.
[0045] Preparation of nanocellulose: prepare hydrochloric acid with a concentration of 15 mol / L, take 5 g of microcrystalline cellulose (Shanghai Guanchuang Biology), add it to 150 mL of hydrochloric acid solution, heat it in a water bath at 80 ± 1 ° C, keep it warm for 10 hours, wash the product with deionized water until it is neutral and then dry it to a moisture content of less than 1.0%, and then use distilled water to prepare a 5% suspension of nanocellulose, use an ultrasonic cell disruptor to ultrasonically treat the suspension at 8000 rpm for 10 minutes, take the suspension and dialyze it several times, and freeze-dry it to obtain nanocellulose. The obtained nanocellulose is tested for particle size potential using a Nano Brook Omni particle size analyzer, and the average size is 100 nm.
[0046] Since nanocellulose itself carries hydrophilic groups, it has both hydrophilic and lipophilic properties. During the emulsification of waterborne polyurethane, nanocellulose spontaneously transfers to the oil-water interface of the hydrophobic polyurethane prepolymer, providing hydrophilicity to the surface of the waterborne polyurethane microspheres and improving their stability in the release agent. The surface of hydrochloric acid-processed nanocellulose is rich in hydroxyl groups and carries a small amount of charge. The electrostatic repulsion between the hydrophilic group charges carried on the surface of the polyurethane microspheres is small. Therefore, a small amount of addition can effectively adsorb on its surface, providing sufficient hydrophilicity, thereby improving the stability of waterborne polyurethane in the release agent. The surface of nanocellulose produced by the sulfuric acid method carries sulfonate groups, resulting in a large amount of surface charge. Although it can improve the antistatic properties of the release film, it is not as effective as the hydrochloric acid-processed nanocellulose in terms of the stability and sustainability of waterborne polyurethane.
[0047] Example 1
[0048] Calculated by weight, the super-heavy release agent for optical display includes 10 parts of water-based chlorinated polypropylene, 3 parts of water-based polyurethane, 0.65 parts of antistatic agent, 0.016 parts of nanocellulose and 6.5 parts of solvent.
[0049] The waterborne polyurethane is sample 1 prepared by the above preparation method. The antistatic agent is polyaniline doped with camphorsulfonic acid. The nanocellulose is prepared by acid hydrolysis using hydrochloric acid. The solvent is isopropanol and the second deionized water, and the mass ratio of isopropanol to the second deionized water is 2.5:1.
[0050] The super heavy release film for optical display comprises a substrate layer and a release layer, wherein the release layer is prepared by curing the super heavy release agent for optical display, wherein the substrate layer is Lucky FP21, and the layer thickness is 50 μm.
[0051] The preparation method of the super heavy release film for optical display comprises the following steps:
[0052] S1: preparing a substrate layer and the above-mentioned super heavy release agent for optical display;
[0053] S2: The super heavy release agent is coated on the surface of the substrate layer using a 400-line diagonal micro-concave roller at a coating speed of 20 m / min to form an uncured release layer;
[0054] S3: Dry and solidify the release layer in an oven. The oven has 6 sections, each section is 4 meters long, and the continuous drying temperatures are set to 70°C, 95°C, 110°C, 120°C, 130°C, and 95°C in sequence. S4: Roll up and mature. The mature temperature is 60°C and the time is 24 hours.
[0055] The thickness of the release layer was 0.7 μm.
[0056] Example 2
[0057] Example 2 is based on Example 1, except that the waterborne polyurethane is sample 2 prepared by the above preparation method. Other things remain unchanged, including the process.
[0058] Example 3
[0059] Example 3 is based on Example 1, except that the waterborne polyurethane is sample 3 prepared by the above preparation method. Other things remain unchanged, including the process.
[0060] Example 4
[0061] Example 4 is based on Example 1, except that the waterborne polyurethane is sample 4 prepared by the above preparation method. Other things remain unchanged, including the process.
[0062] Example 5
[0063] Example 5 is based on Example 1, except that, by weight, the super heavy release agent for optical display includes 10 parts of water-based chlorinated polypropylene, 2 parts of water-based polyurethane, 0.65 parts of antistatic agent, 0.016 parts of nanocellulose and 6.5 parts of solvent.
[0064] Comparative Example 1
[0065] Comparative Example 1 is based on Example 1, except that the super heavy release agent for optical display does not include nanocellulose.
[0066] Comparative Example 2
[0067] Comparative Example 2 is based on Example 1, except that, by weight, the super-heavy release agent for optical display includes 10 parts of aqueous chlorinated polypropylene, 1 part of aqueous polyurethane, 0.65 parts of antistatic agent, 0.016 parts of nanocellulose and 6.5 parts of solvent.
[0068] Comparative Example 3
[0069] Comparative Example 3 is based on Example 1, except that the waterborne polyurethane is prepared by the above-mentioned preparation method as Sample 5. Other things remain unchanged, including the process.
[0070] Performance Testing
[0071] (1) Residual bonding rate: Use Nitto 31B tape to test the residual bonding rate;
[0072] (2) Peel force: Tensile test was performed after 20 min of lamination using Nitto 31B tape (the force value detected at a peeling speed of 300 mm / min at an angle of 180°);
[0073] (3) Resistance: According to ASTM D257, using the American TREK 152-1 surface resistance tester; after six months, the resistance value of the release layer of the release film was tested again to determine the sustainability of the antistatic property;
[0074] (4) Stability of release agent: After six months, invert the sample bottle containing the sample to observe whether there is precipitation;
[0075] (5) Adhesion: Draw a vertical line every 1mm*1mm on the surface of the release layer of the release film, and judge the adhesion between the release layer and the substrate layer according to the extension of the scratch. The adhesion is divided into 0 to 4 levels, where 0 means that a small piece of the release layer is peeled off at the cut and intersection, and the actual damage in the grid area is less than 5%; 1 means that the edge of the cut and intersection is peeled off by 5 to 15%; 2 means that the edge of the cut and intersection is partially peeled off or a large area is peeled off, and the peeled area is 16 to 35%; 3 means that part of the square is peeled off, and the peeled area is 36 to 65%; 4 means that the peeled area is greater than 65%. The lower the adhesion level, the better the adhesion of the ink layer on the release layer.
[0076] The measurement results of the embodiments and comparative examples are shown in the table:
[0077]
[0078] In Example 2, compared with Example 1, the reduction in the content of degraded oligomers of polyethylene terephthalate has a negative impact on the heat resistance of the release layer.
[0079] In Example 3, compared with Example 1, the content of degraded oligomers of polyethylene terephthalate is increased, thereby increasing the crosslinking density of the release layer and improving the heat resistance of the release layer, but reducing the peeling force.
[0080] Compared with Example 1, the viscosity of the aqueous polyurethane prepared by using an alcohol small molecule chain extender is reduced, but the flexibility of the release layer is improved.
[0081] Compared with Example 1, the amount of waterborne polyurethane added in Example 5 is reduced, which has a negative effect on the peeling force.
[0082] Compared with Example 1, in Comparative Example 1, nanocellulose is not added to the release agent, which may easily lead to instability and hydrolysis of the waterborne polyurethane, and have a negative impact on the performance of the release film.
[0083] Compared with Example 1, in Comparative Example 2, the amount of waterborne polyurethane added is too small, which has a negative effect on the peeling force and heat resistance, and also leads to a decrease in the content of polyethylene terephthalate degradation oligomers, which has a negative effect on the adhesion between the release layer and the substrate layer.
[0084] Compared with Example 1, the waterborne polyurethane in Comparative Example 3 does not contain polyethylene terephthalate degradation oligomers, which has a negative effect on the adhesion between the release layer and the substrate layer.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An ultra-heavy release agent for optical display, characterized in that: Calculated by weight, it includes 10 parts of water-based chlorinated polypropylene, 2-4 parts of water-based polyurethane, 0.5-0.8 parts of antistatic agent, 0.01-0.02 parts of nanocellulose and 4-8 parts of solvent; The waterborne polyurethane comprises polyethylene terephthalate degradation oligomers, and the polyethylene terephthalate degradation oligomers are hydroxyl-terminated oligomers terminated by neopentyl glycol and / or dipropylene glycol.
2. The super-heavy release agent for optical display according to claim 1, characterized in that: The antistatic agent is polyaniline doped with camphorsulfonic acid.
3. The super heavy release agent for optical display according to claim 1, characterized in that: The nanocellulose is prepared by acid hydrolysis using a hydrochloric acid method.
4. The super-heavy release agent for optical display according to claim 1, characterized in that: The waterborne polyurethane is prepared by using polyol, polyisocyanate, small molecule chain extender, hydrophilic chain extender, salt former and first deionized water.
5. The super heavy release agent for optical display according to claim 1, characterized in that: The small molecule chain extender is an amine small molecule.
6. The super-heavy release agent for optical display according to claim 4, characterized in that: The polyol further comprises polytetramethylene glycol, the polyisocyanate is isophorone diisocyanate, the molar ratio of polytetramethylene glycol to isophorone diisocyanate is 1:(1.15-1.25), and the added amount of the polyethylene terephthalate degradation oligomer is 2.8%-3.5% of the mass of the polyisocyanate.
7. The super heavy release agent for optical display according to claim 1, characterized in that: The solvent is isopropanol and a second deionized water, and the mass ratio of the isopropanol to the second deionized water is (2-3):
1.
8. An ultra-heavy release film for optical display, comprising a substrate layer and a release layer, characterized in that: The release layer is prepared by curing the super-heavy release agent for optical display according to any one of claims 1 to 7.
9. A method for preparing an ultra-heavy release film for optical display, characterized in that: The following steps are involved: S1: configuring a substrate layer and the super-heavy release agent for optical display according to any one of claims 1 to 7; S2: The super heavy release agent is coated on the surface of the substrate layer to form an uncured release layer; S3: Dry and solidify the release layer, and the continuous drying temperatures are set in sequence as follows: 70±5°C, 95±5°C, 110±5°C, 120±5°C, 130±5°C, 95±5°C; S4: rolling and aging, wherein the aging temperature is 58-63° C. and the time is more than 24 hours.
10. The method for preparing an ultra-heavy release film for optical display according to claim 9, characterized in that: The release layer has a thickness of 0.5-1 μm.